Playing away to win at home - Dermot Leahy; Stephen Pavelin (University College Dublin, UCD School of Economics, 2006)
This paper presents a model of the interaction between two rival firms based in the same country. Each firm must decide how to serve a foreign market (export or foreign production) and how much to invest in a corporate-wide asset that reduces production costs and/or augments the willingness-to-pay for their product. In this scenario, the firms' foreign direct investment decisions are interdependent. Furthermore, strategic motives for FDI relate not to a firm's domestic, as well as foreign, market profits. One possibility is that a firm sets up overseas production even though its foreign market profits would be higher by exporting.
hdl:10197/1271
Keywords: F23; L13; O30; 330; Foreign direct investment; Multinational firm; R&D; Oligopoly